Physical activity indicators during a school day with and without physical education class and health among chilean students - Sepúlveda Martin, Sonia (2022)
High obesity rates and the increase in sedentary time among schoolchildren have direct consequences on the prevalence of non-communicable diseases in adulthood. The school environment is an opportunity to deal with these risk factors, and the importance of physical education classes is critical. The object of this study was to compare the level of physical activity, energy expenditure and sedentary time between a day with physical education class and one without, among first- to third-grade children. This is a non-experimental, analytic, cross-cutting study with a deliberate sample of 46 schoolchildren. Body Mass Index (BMI), physical activity, energy expenditure and sedentary time were measured with accelerometry on school days with and without physical education class. Wilcoxon’s non-parametric test was used to determine differences between school days (p < .05). The results show that schoolchildren had a moderate level of physical activity (3.03 MET) during a day with physical education class, and a light level (2.32 MET) during a school day without physical education class. Students in a school day with physical education class had higher levels of moderate ( Z = -4.430; p < .0001), energetic (Z = -5.403; p < .0001) and highly energetic (Z = -3.940; p < .0001) physical activity, and their sedentary time was lower ( Z = -4.149; p < .0001) as compared to a day without physical education time. The conclusion is that, even though schoolchildren have higher physical activity, higher energy expenditure and lower sedentary time during a day with physical education class, this performance proves insufficient as compared to international recommendations for health.